Identification of an Alternative rRNA Post-transcriptional Maturation of 26S rRNA in the Kingdom Fungi - Navarro-Ródenas, Alfonso; Carra, Andrea; Morte, Asunción (Frontiers in Microbiology, 2018)
Despite of the integrity of their RNA, some desert truffles present a non-canonical profile of rRNA where 3.3kb is absent, 1.8kb is clear and a band of 1.6kb is observed. A similar rRNA profile was identified in organisms belonging to different life kingdoms, with the exception of the Kingdom Fungi, as a result of a split LSU rRNA called hidden gap. rRNA profiles of desert truffles were analysed to verify the presence of the non-canonical profile. The RNA of desert truffles and yeast were blotted and hybridized with probes at LSU extremes. RACE of LSU rRNA was carried out to determine the LSU rRNA breakage point. LSU rRNA of desert truffles presents a posttranscriptional cleavage of five nucleotides that generates a hidden gap located in domain D7. LSU splits into two molecules of 1.6 kb and 1.8 kb. Similar to other organisms, a UAAU tract, downstream of the breakage point, was identified. Phylogenetic comparison suggests that during fungi evolution mutations were introduced in the hypervariable D7 domain, resulting in a sequence that is specifically posttranscriptional cleavaged in some desert truffles.